Novel roles for class II Phosphoinositide 3-Kinase C2ß in signalling pathways involved in prostate cancer cell invasion. - Mavrommati, I.; Cisse, O.; Falasca, Marco; Maffucci, T. (Nature Publishing Group, 2016)
Phosphoinositide 3-kinases (PI3Ks) regulate several cellular functions such as proliferation, growth, survival and migration. The eight PI3K isoforms are grouped into three classes and the three enzymes belonging to the class II subfamily (PI3K-C2a, ß and ?) are the least investigated amongst all PI3Ks. Interest on these isoforms has been recently fuelled by the identification of specific physiological roles for class II PI3Ks and by accumulating evidence indicating their involvement in human diseases. While it is now established that these isoforms can regulate distinct cellular functions compared to other PI3Ks, there is still a limited understanding of the signalling pathways that can be specifically regulated by class II PI3Ks. Here we show that PI3K-C2ß regulates mitogen-activated protein kinase kinase (MEK1/2) and extracellular signal-regulated kinase (ERK1/2) activation in prostate cancer (PCa) cells. We further demonstrate that MEK/ERK and PI3K-C2ß are required for PCa cell invasion but not proliferation. In addition we show that PI3K-C2ß but not MEK/ERK regulates PCa cell migration as well as expression of the transcription factor Slug. These data identify novel signalling pathways specifically regulated by PI3K-C2ß and they further identify this enzyme as a key regulator of PCa cell migration and invasion.